A Play Between Fiction and Non-fiction: Retelling a Story of Exile and Disappearance in Missing (una investigación) (2009) by Alberto Fuguet. - LAZO-GONZÁLEZ, DENISSE (Bulletin of Hispanic Studies (1475-3839), 2021)
This article explores the way in which Missing (una investigación) plays with the limits between fiction and non-fiction in dealing with two of the most prominent issues of the politico-historical Chilean context of the twentieth century: exile and disappearance. It does so through a close reading of the novel's narrative form and its relationship to the context that the novel addresses. It attempts to demonstrate that, despite its setting outside Chile and an author who is apparently not interested in ideological debates, the novel is charged with local Chilean socio-political issues inherited from the second half of the twentieth century and presents us with an alternative approach to those issues, as well a problematic reading of them.